Proactivity as a Predictor of Social Sensitivity in University Students - Eyüp Çelik; Kübra Dombak; Golsa Parvizi Ağaya; Samet Makas (Sakarya University Journal of Education)
This study investigated the relationship between proactive personality and social sensitivity among university students. The sample comprised 543 participants (445 women, 98 men). Data were collected using the Social Sensitivity Scale and the Brief Proactive Personality Scale. Correlation analysis revealed a significant positive relationship between social sensitivity and proactive personality. Regression analysis further indicated that proactive personality is a significant predictor of social sensitivity. Additionally, findings showed that married participants exhibit significantly higher social sensitivity than those in dating relationships. T-test findings illustrated women had higher social sensitivity levels compared to men.